GENDER AND LEADERSHIP IN EDUCATIONAL INSTITUTIONS - Искиндирова, Ж.Ж. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
Compared to males' age-old experience in leadership, women are just on their way to learning this privilege. Despite the long term existing of gender studies, women face many barriers during their career. Thus, becoming a female leader in education is a progressive step towards developing leadership and recognising its diversity. This study considers the gender distribution of leadership positions in educational institutions. Here will be presented an attempt to various reasons and barriers of gender inequality in educational leadership.
Keywords: Educational institution; gender study; equality; leadership; educational policy